2010
DOI: 10.1021/jp9103596
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of N2O Formation During NO Reduction on the Au(111) Surface

Abstract: Density functional theory calculations have been performed to elucidate the mechanism of N2O formation over the Au(111) surface during NO reduction. It is shown that the dissociation of NO into an N atom and an O atom involves a barrier as high as 3.9 eV, implying that the formation of N2O does not occur via the direct dissociation mechanism of NO. Alternatively, we find that the reaction may occur via a dimer mechanism; i.e., two NO molecules initially associate into a dimeric (NO)2, which then dissociates in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 44 publications
5
65
0
Order By: Relevance
“…10,17,29,43 One of the intermediates observed in the reduction of NO with CO is NCO, suggesting NO dissociation followed by reaction of an N adatom with CO. Interestingly, the NCO intermediate was not observed during the NO adsorption on Au/TiO 2 ; [44][45][46][47] but the formation of dinitrosyl complexes attached to the same Au atom, e.g., Au(NO) 2 species, either in the presence or in the absence of CO, 44,45 was detected. This suggests that the energy required to cleave the N-O bond is very high on Au/TiO 2 catalysts, which is in agreement with the results from the density functional theory (DFT) studies by Wang et al 48 for NO adsorption on the Au(111) surface. They correlated the formation of (NO) 2 dimers with the high activation energy barrier for the NO dissociation on Au(111) and suggested that the (NO) 2 dimers evolve to N 2 O.…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…10,17,29,43 One of the intermediates observed in the reduction of NO with CO is NCO, suggesting NO dissociation followed by reaction of an N adatom with CO. Interestingly, the NCO intermediate was not observed during the NO adsorption on Au/TiO 2 ; [44][45][46][47] but the formation of dinitrosyl complexes attached to the same Au atom, e.g., Au(NO) 2 species, either in the presence or in the absence of CO, 44,45 was detected. This suggests that the energy required to cleave the N-O bond is very high on Au/TiO 2 catalysts, which is in agreement with the results from the density functional theory (DFT) studies by Wang et al 48 for NO adsorption on the Au(111) surface. They correlated the formation of (NO) 2 dimers with the high activation energy barrier for the NO dissociation on Au(111) and suggested that the (NO) 2 dimers evolve to N 2 O.…”
Section: Introductionsupporting
confidence: 90%
“…48) on Au(111) and −0.50 eV on Au(110), or on the Ag doped gold surfaces, i.e., −0.36 eV on the Ag@Au(111) surface and −0.45 eV on the Ag@Au(110) surface, to high adsorption energy values as that calculated for NO interaction with the Ir@Au(110) surface (value of −3.26 eV). Adsorption energies more negative than −2.0 eV were also calculated for Ni and Rh doped Au surfaces.…”
Section: A Adsorption Of No and Co-adsorption Of N + Omentioning
confidence: 78%
See 1 more Smart Citation
“…What is the main pathway for N 2 formation? In addition, interestingly, (NO) 2 dimer was observed at room temperature by using infrared spectroscopy on Pd(1 1 1) surface recently, as demonstrated in the literature on some other surfaces including Au [4], Ag [26], Cu [27][28][29], Mo [30], Rh [31], Al 2 O 3 [32], MgO [33], and Si-doped graphene [34]. In experiment, N 2 O was observed at low temperature on ZrO 2 -supported Pd nanocatalysts [3].…”
Section: Introductionmentioning
confidence: 60%
“…The emission of NO not only causes a series of environmental problems such as photochemical smog, acid rain and ozone depletion [1][2][3], but also has adverse effect on humans. Therefore, the catalytic removal of NO has become one of the most important problems for air pollution control and attracted remarkable attention in both academic and applied research fields [4]. In the automotive industry, platinum group metals (PGMs) such as Pt, Pd, and Rh as the main components are involved in the three-way catalysts, which have often been used for the catalytic reduction of NO for several decades [5,6].…”
Section: Introductionmentioning
confidence: 99%